Students’ Perceptions in Online Learning during the Covid-19 Pandemic in Speaking Context - Eka Pratiwi Yunianti; , Faidzun Jatur Priona (Aisyah Journal of English Language Teaching (AIJELT), 2023)
The purpose of this study was to investigate how students felt about using online courses during the epidemic. Eighteen students from Aisyah University of Pringsewu were surveyed for this study. To get a more nuanced understanding of the respondents' perspectives, a descriptive qualitative approach was adopted. The findings highlight the importance of having reliable and constant connection to the internet for effective online education. Most students have a poor impression of online education due to three key factors: the quality of the instructional design and delivery, the importance of teacher involvement, and the lack of student engagement. In conclusion, student opinion of online education is indifferent. Therefore, it is essential to provide students with as much transparent assistance with the technological components of online learning as feasible. In addition, schools should give students with free internet data bundles so that everyone has the same access to online resources. Finally, for an online classroom to be successful, teachers need to constantly reflect on and adjust their methods of instruction.